Application Development for Monitoring and Evaluation On Early Child Growth and Development in Lombok - sudirman sudirman (TIRAI EDUKASI: Jurnal Pendidikan, 2020)
In Indonesia data were scattered in various sectors and yet no real-time data management was set up in the time of the study. This study reported the staging of process on developing a mobile application for real-time data management information system on monitoring and evaluation of child growth and development in early childhood education. Application for monitoring and evaluation is an application that can help tracking child growth and development and assist teacher or field worker in monitoring and feedback related to child growth and development services. A study was carried out to gather necessary information through data mapping, in-depth interviews with key stakeholders, document reviews, application development, direct entry in the field using mobile development, application testing and analysis that was conducted on for 97 respondents in Pringgarata Subdistrict, Central Lombok . To obtain a full picture on child growth, development in early childhood education, data on child growth and education shall be mapped and linked in one application. We introduce a mobile app to systematically compile the individual as well as group data (i.e. village or district profiles) across different aspects of child life, ranging from nutrition, health, education, etc. Using a tablet PC or mobile phone, data could be easily entered at anytime (real-time data) by the person. Due to still poor infrastructure at the grass root level, the system also allows a safety store offline that could automatically link to server when network connection is available. The immediate data entry will provide real-time data report that could be accessed by any relevant stakeholders at any levels to response accordingly. However, to avoid misuse of data, the access will also be restricted with a secured login system. Based on the study, this application is easily applicable for real-time monitoring and evaluation on early child growth and development.